Adsorption studies of KOH-modified hydrochar derived from sugarcane bagasse for dye removal: Kinetic, isotherm, and thermodynamic study - Lestari, Dwi Indah; Yuliansyah, Ahmad Tawfiequrrahman; Budiman, Arief (Communications in Science and Technology, 2022)
Toxicity of methylene blue (MB) in water bodies has a negative effect on environment and living organisms. The presence of MB in water could last longer in view of the non-biodegradable characteristic. In this study, hydrochar was used as adsorbent to remove MB from aqueous solution. Hydrochar derived from bagasse was successfully prepared by hydrothermal carbonization treatment at temperature of 270oC, and pressure of 10 Bar for 30 minutes. For enhancing the adsorption ability, hydrochar was activated by adding KOH that was able to increase the percent removal by ~11%. The hydrochar was characterized using FTIR before and after adsorption. The results showed that the dominant functional groups of hydrochar included O-H, C=O, -O- and aromatic compounds. Whereas, the functional group of azo groups such as N-H and N=N appeared after adsorption. The maximum adsorption capacity (Qmax) was 5.1204 mg/g, while the adsorption isotherm of MB onto hydrochar followed the Langmuir and Freundlich model. The adsorption mechanism belongs to chemical adsorption, and the rate of diffusion can be neglected because the adsorption kinetics fitted well with pseudo-second order and the value of k2 > kdif > k1. Thermodynamic studies indicated that the adsorption process is classified as endothermic and reversible at room temperature. The results showed that hydrochar could be the alternative adsorbent for removing MB in wastewater. In addition, sugarcane bagasse has a great potential as feedstock of hydrochar.